2000
DOI: 10.1177/088626000015011006
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Professional Football Games and Domestic Violence in Los Angeles County

Abstract: This article explores the association between professional football games and domestic violence (DV) by performing an ecological time trend analysis of Los Angeles Sheriff Department's (LASD) data from January 1, 1993, to December 31, 1995. Mean weekly DV dispatch increase in the 1993-1994 football season was 69% during nonfootball season compared with 100% during football season (p = 0.09), 147% during playoff weeks, and 264% during Super Bowl (SB) week. Mean weekly increase over the entire time period was 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
2
25
1
Order By: Relevance
“…For example, in the United States, Sachs and Chu (2000) observed an increase in domestic violence dispatches by the Los Angeles Sheriff's Department during selected American football game days, while Lin (2007) found increases in burglary and vehicular theft and a moderate increase in theft from a vehicle on an American football game day compared to a non-game day in Seattle. Rees and Schnepel (2009) also found an increase in assaults, vandalism, liquor law violations, driving under the influence, and disorderly conduct on American college football game days across a large swath of the United States.…”
Section: Understanding the Sporting Events/crime Linkagementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the United States, Sachs and Chu (2000) observed an increase in domestic violence dispatches by the Los Angeles Sheriff's Department during selected American football game days, while Lin (2007) found increases in burglary and vehicular theft and a moderate increase in theft from a vehicle on an American football game day compared to a non-game day in Seattle. Rees and Schnepel (2009) also found an increase in assaults, vandalism, liquor law violations, driving under the influence, and disorderly conduct on American college football game days across a large swath of the United States.…”
Section: Understanding the Sporting Events/crime Linkagementioning
confidence: 99%
“…Research in several countries has investigated the relationship between the occurrence of sporting events and crime (Braaf and Gilbert 2007;Drake and Pandey 1996;Fernquist 2000;Kirk 2008;Lin 2007;Sachs and Chu 2000). A wide variety of crime types has been considered and, overall, this body of literature has largely demonstrated that the occurrence of a sporting event is generally correlated with an increase in the number of crimes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sachs and Chu (2000) failed to find a statistically significant association between professional football games and domestic violence dispatches in the county of Los Angeles over a three-year period (1993)(1994)(1995). White et al (1992) examined the relationship between games played by The Washington Redskins, a professional football team, and emergency room admissions at two hospitals in northern Virginia over a twoyear period (1988)(1989).…”
Section: Introductionmentioning
confidence: 98%
“…First, Sachs and Chu (2000) developed the hypothesis that 'Super Bowl Sunday is often the biggest day of the year for domestic violence ' (p. 1192), and subsequently evaluated the relationship between emergency department admissions of women, domestic violence calls to the local police department and local American football team match outcome. Data indicated a trend such that greater domestic violence was identifi ed on match days.…”
Section: Introductionmentioning
confidence: 99%